The multimodal approach and psychotherapy schools - Kertész, Roberto (2005)
There is realized a review of the multimodal therapy created by Arnold Lazarus; describing the condition (state) integrativo present of a person; from the seven manners or variables of the total personality: Biological; affective; sensations; images; cognitive; donductas and social. It he; exposes the multimodal profile as an instrument that discriminates against the only thing; the unrepeatable of every individual. Finally it he; distinguishes the theoretical eclecticism and the technical eclecticism; valuing the contribution of other approaches.